Switchable selectivity in Pd-catalyzed [3 + 2] annulations of γ-oxy-2-cycloalkenones with 3-oxoglutarates: C–C/C–C vs C–C/O–C bond formation - Liu, Yang; Oble, Julie; Poli, Giovanni (Beilstein Journal of Organic Chemistry, 2019)
Two complementary [3 + 2] annulation protocols between 3-oxoglutarates and cyclic γ-oxy-2-cycloalkenones, simply differing on the reaction temperature, are disclosed. These domino transformations allow C–C/O–C or C–C/C–C [3 + 2] annulations at will, via an intermolecular Pd-catalyzed C-allylation/intramolecular O- or C-1,4-addition sequence, respectively. In particular, exploiting the reversibility of the O-1,4-addition step, in combination with the irreversible C-1,4-addition/decarboxylation path, the intramolecular conjugate addition step could be diverted from the kinetic (O-alkylation) to the thermodynamic path (C-alkylation) thanks to a simple temperature increase. Crucial for the success of this bis-nucleophile/bis-electrophile [3 + 2] annulation is its well-defined step chronology in combination with the total chemoselectivity of the former step. This [3 + 2] C–C/O–C bond forming annulation protocol could be also extended to 1,3,5-triketones as well as 1,3-bis-sulfonylpropan-2-one bis-nucleophiles.
Keywords: 1,4-addition; annulation; decarboxylation; palladium; Pd-catalyzed allylation reaction